The Curious Case of Rat Tail Syndrome: A Rare Clinical Presentation - B, Sagarika; Pattanshetti, Swapnil Annasaheb; Shivapujimath, Manjunath; Gautam, Vineeta (Journal of Neonatal Surgery, 2025)
Background: Rat tail syndrome is a descriptive term occasionally used to refer to rare distal spinal hypoplasia resembling a thin, tapering tail. It often falls under the spectrum of caudal regression syndrome (CRS), a rare congenital disorder characterized by partial or complete agenesis of the sacrococcygeal spine. CRS is typically associated with maternal diabetes and other syndromic conditions, although idiopathic cases can occur. Case-Presentation: We report the case of a 1-year-old female infant, the first-born child of healthy non-consanguineous parents. She was delivered at term via normal vaginal delivery, with an uneventful perinatal period and no neonatal intensive care requirement. There was no maternal diabetes or antenatal complications. Patient had a swelling since birth which gradually increased in size and during a routine pediatric check-up, abnormal spinal curvature and a blunted gluteal cleft were noted. Neurological examination revealed mild hypotonia in the lower limbs with normal bladder and bowel function. MRI of the lumbosacral spine revealed hypoplastic sacrococcygeal vertebrae, a low-lying conus medullaris ending at L5 and a thickened filum terminale—findings consistent with tethered cord syndrome within the CRS spectrum. The patient underwent successful untethering surgery via laminectomy. Postoperative recovery was uneventful, and at 6- month follow-up, she demonstrated improved tone and independent walking. Conclusion: This case highlights a rare, idiopathic presentation of caudal regression syndrome resembling rat tail morphology in a healthy term infant. Early detection through clinical suspicion and imaging, followed by timely surgical intervention, can significantly improve neurological outcomes and prevent long-term complications